Simplifying and isolating failure-inducing input - Zeller, A.; Hildebrandt, R. (IEEE transactions on software engineering, 2002)
Given some test case, a program fails. Which circumstances of the test case are responsible for the particular failure? The delta debugging algorithm generalizes and simplifies the failing test case to a minimal test case that still produces the failure. It also isolates the difference between a passing and a failing test case. In a case study, the Mozilla Web browser crashed after 95 user actions. Our prototype implementation automatically simplified the input to three relevant user actions. Likewise, it simplified 896 lines of HTML to the single line that caused the failure. The case study required 139 automated test runs or 35 minutes on a 500 MHz PC.